Properties of resin-impregnated sugar palm fibre- reinforced epoxy composites - Mohd Nor Munawar, Nur Sofeana Zulaika (2018)
Natural fibres are produced in abundance and readily available as compared to synthetic fibre which is expensive and takes a longer time to degrade. Sugar palm (Arenga pinnata) fibre is one of potential locally available natural fibre belongs to the Palmae family. This study focuses on the effect of vacuum resin impregnation on sugar palm fibre (SPF) using epoxy, vinyl ester (VE) and polyester (PE) as the impregnating agents. Initially, the SPF is impregnated with epoxy, VE and PE where the fibres are placed in a beaker filled with the specific impregnating agent and vacuum at a constant impregnation pressure of 600 mmHg for 5 minutes. Then, the fibres are drained to remove the excess resins and cured in an oven for 30 minutes at a temperature of 140°C before tested for its physical and tensile properties. The impregnated fibres are used to fabricate into a composite with epoxy as the matrix. The physical, mechanical and chemical composition of the composites is evaluated. It is found that the single SPF impregnated with epoxy offered greater value of tensile strength and modulus followed by SPF/VE and SPF/PE. The scanning electron micrograph indicates that epoxy resin displays better impregnation on sugar palm fibre compared to the other thermosetting resins. FT-IR proves the existence of lignocellulosic materials in the fibres such as lignin, cellulose and hemicellulose. Similar results are observed for the resin impregnated SPF reinforced epoxy composite, where their tensile properties showed a better performance. Meanwhile, under flexural testing, all the impregnated SPF reinforced epoxy composites showed a reduction in their values indicating that the composite is not suitable for bending application. SPF/VE reinforced epoxy composite has the best flexural strength while SPF/Epoxy reinforced epoxy composite has the best flexural modulus for impregnated SPF composites. SPF/PE reinforced epoxy composite resulted in the worst reading for both tensile and flexural testing. The dimensional stability for resin impregnated SPF reinforced epoxy composites has significantly improved. Both water absorption (WA) and thickness swelling (TS) of all the impregnated fibre composite are reduced. SPF/Epoxy reinforced epoxy composite has the most reduction in value for both testings. On top of that, the density and specific gravity (SG) for the impregnated SPF reinforced epoxy also showed a reduction in their reading. SPF/VE reinforced epoxy composite has the highest reduction followed by SPF/PE reinforced epoxy composite and SPF/Epoxy reinforced epoxy composite. Overall results showed that both fibre and composite part shows that VE is the best impregnating agent while SPF/PE gave the worst result. It can be concluded that treating the SPF with VE will enhance the properties of sugar palm fibre composite.